2015
DOI: 10.17970/jrem.15.150204.id
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Customer Engagement Terhadap Kepuasan Pelanggan Dan Kepercayaan Merek Serta Dampaknya Pada Loyalitas Merek

Abstract: ABSTRAKSICustomer engagement baru-baru ini muncul dalam literatur akademis dan diskusi praktisi sebagai perspektif baru dalam penerapan customer relationship management yang bertujuan membangun loyalitas merek. Hal ini didorong munculnya saluran interaksi baru, yaitu media sosial dan semakin populernya internet, yang memungkinkan perusahaan dapat berinteraksi lebih intensif dengan pelanggannya. Namun demikian, penyelidikan empiris tentang customer engagement masih relatif terbatas. Penelitian ini bertujuan men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 8 publications
2
9
0
5
Order By: Relevance
“…This brand loyalty occurs after consumers get satisfied with the products and services given by a brand, and they trust the brand so that it is hoped that customers will make repeat purchases, and customers will think again and will not even switch to another brand. Previous research has found that customer engagement influenced customer satisfaction and brand trust positively but had no effect on brand loyalty (Rahmawati & Aji, 2015). Hwang et al (2021) unveiled that customer satisfaction and trust affected customer behavior in terms of loyalty; customer engagement was found to be positively associated with customer trustworthiness (Kosiba et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
“…This brand loyalty occurs after consumers get satisfied with the products and services given by a brand, and they trust the brand so that it is hoped that customers will make repeat purchases, and customers will think again and will not even switch to another brand. Previous research has found that customer engagement influenced customer satisfaction and brand trust positively but had no effect on brand loyalty (Rahmawati & Aji, 2015). Hwang et al (2021) unveiled that customer satisfaction and trust affected customer behavior in terms of loyalty; customer engagement was found to be positively associated with customer trustworthiness (Kosiba et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
“…According to previous research conducted by (Rahmawati and Aji 2015) using 140 samples, it shows that customer engagement has a positive effect on brand trust, but has no effect on brand loyalty because the hypothesis test results show the value of C.R. amounting to 5.073 ≥ 1.96 and a significance of P of 0.000 ≤ 0.05.…”
Section: Customer Engagement To Brand Trustmentioning
confidence: 92%
“…Purnami (2017) menyatakan loyalitas merek berpengaruh signifikan terhadap customer engagement, dengan begitu semakin tinggi persepsi nilai dari konsumen terhadap produk yang ditawarkan di media sosial maka semakin tinggi pula keinginan konsumen untuk terlibat dalam aktivitas customer engagement yang dilakukan perusahaan. Berbeda dengan Rahmawati & Sanaji, (2015) menyatakan customer engagement tidak berpengaruh terhadap loyalitas merek. Berdasarkan paparan di atas maka digunakan variabel mediasi karena loyalitas merek dan trust merupakan mediator yang baik.…”
Section: Pendahuluanunclassified